The Emerging Applications of Nanotechnology in Neuroimaging: A Comprehensive Review - Faiz, Khunza; Lam, Fred C.; Chen, Jay; Kasper, Ekkehard M.; Salehi, Fateme (Frontiers in Bioengineering and Biotechnology, 2022)
Neuroimaging modalities such as computer tomography and magnetic resonance imaging have greatly improved in their ability to achieve higher spatial resolution of neurovascular and soft tissue neuroanatomy, allowing for increased accuracy in the diagnosis of neurological conditions. However, the use of conventional contrast agents that have short tissue retention time and associated renal toxicities, or expensive radioisotope tracers that are not widely available, continue to limit the sensitivity of these imaging modalities. Nanoparticles can potentially address these shortcomings by enhancing tissue retention and improving signal intensity in the brain and neural axis. In this review, we discuss the use of different types of nanotechnology to improve the detection, diagnosis, and treatment of a wide range of neurological diseases.